Comparing Balance Performance on Force Platform Measures in Individuals with Parkinson’s Disease and Healthy Adults - Cathy C. Harro; Amanda Kelch; Cora Hargis; Abigail DeWitt (Parkinson's Disease)
Introduction. Postural instability is a known contributing factor to balance dysfunction and increased fall risk in those with Parkinson’s disease (PD). Computerized posturography employing a force platform system provides objective, quantitative assessments of postural control impairments. This study examines balance performance as measured by force platform (FP) tests in persons with PD compared to age-matched healthy adults. Secondarily, we examine if these FP measures provide diagnostic and clinically meaningful information about the underlying balance impairments in the PD population. Methods. Participants—42 individuals with PD (Hoehn and Yahr stage = 2.33 ± 0.77) and 55 age-matched healthy adults—were assessed on three standardized balance measures on a computerized force platform system. Between groups, comparisons of FP performance were analyzed using independent t-test. Within the group, comparisons for the PD cohort were analyzed using ANOVA for comparing disease stage and Mann–Whitney U test for PD subtypes. Results. The PD cohort demonstrated significantly greater postural instability on the sensory organization test (SOT) measures (P=0.013, CI-95% = 1.286 to 10.37) and slower movement velocity on the limits of stability (LOS) test (P=0.001, CI-95% = 0.597 to 1.595) than the healthy cohort, suggesting that these tests were sensitive to detect sensory integration and voluntary postural control deficits in the PD cohort. Within the PD group, the SOT differentiated between H&Y stages 1–3. The motor control test (MCT) detected changes in reactive postural control mainly in later disease stages. All three FP tests distinguished between PD subtypes, with the Posture Gait Instability subtype demonstrating poorer balance performance than Tremor Dominant subtype. Conclusion. These findings suggest FP measures provide clinically meaningful, diagnostic information in the examination of balance impairments in individuals with PD. FP measures may inform clinicians regarding intrinsic balance deficits and guide them in designing targeted balance interventions to reduce fall risk in persons with PD.